Genotoxic effects induced by Cd+2, Cr+6, Cu+2 in the Gill and Liver of Odontesthes bonariensis (Piscies, Atherinopsidae) - Gasulla, Javier (2016)
Genotoxic effects of Cd?2, Cr?6, and Cu?2 on the gill and liver of the Argentinean Silverside (Odontesthes bonariensis) were studied using the comet assay and in relation with the metal tissue accumulation. Fish were exposed to three waterborne concentrations of each metal for 2 and 16 days. Genotoxicity was assessed by the single cell gel electrophoresis (comet assay). After 2 days, significant increase of the genetic damage index (GDI) was only observed in the gill of fish exposed to Cr?6 and Cu?2, and the LOECs were 2160 nM and 921.1 nM, respectively. The gill LOEC for Cd?2 by 16 days was 9.4 nM. In the liver, LOECs were obtained only for Cd?2 and Cr?6 and were 9.4 and 2160 nM, respectively. The three metals were able to induce genotoxic effects at environmentally relevant concentrations and the gill was the most sensitive organ.